Anti-bolshevism and antisemitism: the Catholic church in Germany and national docialist ideology 1936-1937 - Besier, Gerhard (The journal of ecclesiastical history, 1992)
In his essay ‘Judaism and Christianity in the ideology and politics of National Socialism’ Klaus Scholder outlined the basic principles of Hitler's world view and examined his perception of the relationship between Christianity and antisemitism. According to Hitler, there could be no doubt that Christian leaders, given the nature of their beliefs, should be active exponents of antisemitism. He revitalised the old motif of the Jews as ‘Christ killers’ and described Jesus as ‘a leader of the people’ who ‘opposed Jewry’. Because of this he had been murdered on the initiative of the Jews and the Jew Paul ’refined, falsified and exploited the teaching of the Galilean for his own ends’.